Sheep dietary preferences in targeted grazing: demographic, management, and weather effects in northern mixed-grass prairie - Kersh, Aaron J.; Fraley, Hannah M.; Scasta, J. Derek; Derner, Justin D.; Lima, Paulo de Mello Taveres; Stewart, Whit C. (Frontiers in Veterinary Science, 2024)
Diet selection and composition of sheep target grazing plains larkspur (Delphinium geyeri Greene) in northern mixed-grass prairie were evaluated during a drought year (2022). Thirteen Rambouillet ewes (3-to 6-year-old, body weight (BW) 76 kg ± 2.9), 14 Dorper ewes (3-to 6-year-old, BW 47 kg ± 1.8), and 123 Dorper ram lambs (<1 year-old, BW 25 kg ± 0.4) were used for targeted grazing. Over the 20-day first phase (mid-May to early June), sheep were subjected to three stock density treatments: (1) high, 40 animal units (AU)/ha, (2) moderate, 20 AU/ha, and (3) light, 13 AU/ha. In the second phase (21 d, early-to late-June), the same sheep grazed four 1.5 ha paddocks sequentially at a very light stock density of 7 AU/ha. Dietary composition was assessed through focal bite count observations at the plant functional group level for phase one only, and dietary composition was estimated through fecal DNA metabarcoding (f.DNA) at the plant species level for both phases. Results indicated a uniformly low preference for larkspur (< 1% in diets). There were no significant effects of breed or age on focal bite count observations of plant functional groups (grasses, forbs, and larkspur), nor were there significant effects of breed or age on f.DNA diet proportions of plant functional groups (p > 0.05). Stock density did influence focal bite count observations, with higher forb intake (p = 0.0004) and lower grass intake (p = 0.009) observed at the moderate density compared to the high density. In phase two, grass and larkspur intake decreased while forb intake increased according to f.DNA (p < 0.01). These findings suggest that moderate stock density, combined with an understanding of plant phenology, precipitation variability, and animal forage preferences can optimize vegetation and animal performance in adaptive targeted grazing management within this ecosystem.